PENGARUH LINGKUNGAN KERJA, KONFLIK KERJA, STRES KERJA, SERTA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI PT. TELKOM INDONESIA,Tbk AREA DENPASAR - Dwi Cahyono, Han (Buletin Studi Ekonomi, 2016)
The effect of work enviroment, work conflict, work stress and leadership to employee perfomance in PT. Telkom Indonesia, Tbk (Denpasar area). Adaptive leadership role and able to interesting for further study, particulary associated with the work environment, work conflict, work stress, leadership, and employees performance. The result showed that: increasing the quality of working enviroment can improve the quality of leadership. Leadership is the dominant factor that can enchance the performance of employees in PT. Telkom Indonesia Tbk Denpasar Area. It is suggested to make the management of an integrated program to solve these gaps, especially respondents who include into the low category, because it can lead to word of mouth (WOM) employees who can influence leadership and employee performance.   Keywords: work environment, work conflict, work stress, leadership, employee performance
Keywords: work environment, work conflict, work stress, leadership, employee performance